2013
DOI: 10.1007/s11605-013-2234-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Intra-abdominal Fluid Collections Following Pancreatic Surgery

Abstract: BackgroundLittle data are available for non-abscess abdominal fluid collections (AFCs) after pancreatic surgery and their clinical implications. We sought to analyze the natural history of such collections in a population of patients subject to routine postoperative imaging.MethodsFrom 1995 to 2011, 709 patients underwent pancreatic resections and routine postoperative monitoring with abdominal ultrasound according to a unit protocol. AFCs were classified as asymptomatic (no interventional treatment), symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
0
33
1
Order By: Relevance
“…Previously, in a study including many types of pancreatic surgery, this rate was reported as approximately 12% in the first week after surgery by US examination [14]. In 2 other studies, abdominal fluid collection was seen in 15% of patients on POD 3 after PD or distal pancreatectomy (DP) [615].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in a study including many types of pancreatic surgery, this rate was reported as approximately 12% in the first week after surgery by US examination [14]. In 2 other studies, abdominal fluid collection was seen in 15% of patients on POD 3 after PD or distal pancreatectomy (DP) [615].…”
Section: Discussionmentioning
confidence: 99%
“…However, when the presence of fistula of any grade (including grade A) was considered, the rate of POPF rose to 69%. Sierzega et al [14] reported this rate as 17% in their 83 patients with early abdominal fluid collection detected by transabdominal US. In another study, peripancreatic fluid collection on POD 3 was associated with any grade of POPF in 88% of patients who underwent PD or DP [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of over 700 patients, 21% developed PCs with up to 35% requiring intervention. 24 Indications for treatment of PCs include symptoms caused by compression on adjacent structures including epigastric pain, early satiety, unintended weight loss, gastroduodenal outlet obstruction (GOO) or biliary obstruction. 7,25 Endoscopic therapy of PCs has become the "new gold standard" due to low risk and improved outcomes when compared to percutaneous and surgical approaches.…”
Section: Pancreatic Fluid Collection Drainagementioning
confidence: 99%
“…Peripancreatic collections can be approached percutaneously as long as the subject is hemodynamically stable and has an acceptable coagulation panel, and there is a safe access route for a needle. Although most of the times the drainage procedure is mandated by serious clinical symptoms, such as fever, leukocytosis, pain, or sepsis, a number of clinically silent abscesses have been reported [27]. Normally, prophylactic broad-spectrum antibiotics are given before all procedures.…”
Section: Interventional Techniquesmentioning
confidence: 99%